PENINGKATAN EKSPRESI INTERLEUKIN (IL)-4 BERHUBUNGAN DENGAN PENURUNAN BAX DAN APOPTOSIS LIMFOSIT PADA BRONKIOLUS DAN PARU MENCIT ASMA - Yuliarto, Saptadi; Kusuma, HMS Chandra; Widjajanto, Edi (Fakultas Kedokteran Universitas Brawijaya, 2009)
Decrease of lymphocyte apoptosis is one factor that leads to chronic airway inflammation in allergic asthma. Previous studies revealed the role of interleukin (IL)-4 in preventing lymphocyte apoptosis; however there are few studies about the role of lymphocyte-Bax and its relationship with IL-4 in asthma. The aim of the study is to demonstrate IL-4 role in preventing lymphocyte apoptosis via lymphocyte-Bax inactivation in bronchioli and lungs of asthmatic mice. It is a randomized control group experimental study . The subject was Balb/c mice that categorized into 2 groups: asthma and non-asthma. Asthma group was sensitized by ovalbumin intraperitoneally in day 0 and 14, followed by inhalation every 2-3 days for 6 weeks. In week 8, all of mice were terminated. The IL-4 and lymphocyte-Bax expression was examined through immunohistochemistry method, whereas lymphocyte apoptosis by TUNEL method. Independent sample t-test, Mann Whitney U test, regression analysis, and path analysis was used in statistical analysis with confident interval 95%. The bronchioli and lungs specimens were obtained from 18 mice (9 in each group). Lymphocyte apoptosis was similar between 2 groups (p=0.1 16), additionally lymphocyte-Bax decreased in asthmatic group (p=0.003). This indicated low activity of lymphocyte apoptosis in asthmatic group.